THE FUNCTION OF THE ILLOCUTIONARY ACT IN A NOVEL ENTITLED ONE OF US IS LYING - Monique Sharon Nayoan; Devi Hellystia (Universitas Gunadarma, 2022)
Humans will always need others to communicate and build a relationship since they are created as social beings. Language enables people to express their thoughts, feelings, and ideas. It helps the hearer to clear up the speaker's intention. Using Leech’s theory (1983), this research aims at analyzing the function of the illocutionary act of Nate Macauley in a novel entitled One of Us Is Lying. The qualitative descriptive method was used as the research design to analyze and describe the function of the illocutionary act of Nate’s utterance. Karen M. McManus’ novel entitled One of Us Is Lying was used as a data source for this research. The data comprised written text (phrases, clauses, and sentences) which was spoken by Nate Macauley. The result indicates from 108 data, all of the illocutionary act’s functions are discovered, there are competitive function (Asking, ordering, and demanding), convivial function (Offering, inviting, greeting, thanking, apologizing, and complimenting), collaborative function (Asserting and reporting), and conflictive function (Accusing and cursing). However, some forms of the function of illocutionary act did not appear, such as begging in competitive function, congratulating in convivial function, announcing and instructing in collaborative function, threatening and reprimanding in conflictive function. The conclusion also implies that a single datum can have several illocutionary act’s functions. In this study, collaborative function is found to be the most frequently used illocutionary act’s function, specifically in a form of asserting. This function is indifferent goal since it is employed to state the truth or the speaker’s opinion regardless of whether it is good or bad